FACTORS THAT AFFECT FINANCING PROFIT-LOSS-LOSS SCHEME) SYARIAH TBK GENERAL BANKING IN INDONESIA - Yolanda; Darwanti, Dhenok; Ratnasih, Cicih (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of this study is to determine the economic aspects of the implementation of financing (Revenue Sharing - Loss). Factors that affect financing (Profit Sharing Schemes - Losses) in Islamic general banking Tbk in Indonesia (in 2011-2017) using the variable Third Party Funds (DPK), Capital/equity, Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Return on assets (ROA) and Financing to Deposit Ratio (FDR). The method of this study is Ordinary Least Square (OLS) with panel data from the eight observed Sharia commercial banks. The approaching model used in this study is the Fixed Effect Model. The results of this study show that Third Party Funds (DPK), Capital / Equity, Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR) have a significant effect on financing (Revenue Sharing - Loss Scheme), while Return on assets (ROA) and Financing to Deposit Ratio (FDR) has no significant effect on financing (Revenue Sharing - Loss).